Level Of Physical Freshness Of Class VII1 Students Of SMP Negeri 48 Pekanbaru - Alim komarudin; Mimi yulianti (FKIP Universitas Islam Indragiri, 2023)
This research aims to determine the level of physical freshness of class VII1 students at SMP Negeri 48 Pekanbaru. The type of this research is descriptive, descriptive research is a research method that seeks to describe the object or subject under research by what it is to systematically describe the facts and characteristics of the object being studied accurately. The population and sample in this research used a purposive sampling technique. The subjects of the sample are 17 male students of class VII1 at SMP Negeri 48 Pekanbaru. The research instrument used is the TKJI test aged 13-15 years. The data analysis technique used is to calculate the categories of physical freshness values obtained by students. Based on the results of calculating the average physical freshness it is known that the physical freshness of class VII1 male students of SMP Negeri 48 Pekanbaru is classified in the Moderate category with an average of 15.65 which lies in the interval of the TKJI value category 14-17. This means that the effectiveness of physical freshness of class VII1 students of SMP Negeri 48 Pekanbaru actually can still be improved by adding exercises and making more complete facilities so that the level of physical freshness of these students can be better and more efficient in learning.